Status Hadith La Wasiyyah li Warith menurut Imam al-Shafiâ€™iy - Imam Supriyadi (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2015)
Abstract: This article backdrop of, first, how's the views of â€ŽImam al-Shafi'iy of the position of the hadith "la wasiyyah li â€Žwarith" to QS. Al-Baqarah (2): 180, and second, how's the â€Žlegal status of the sanad and matan hadith. With a qualitative â€Žapproach and analyze it with hirearkis verification, it was â€Žconcluded that: first, the al-Shafi'iy's view of the position of â€Žthe hadith "la wasiyyah li warith" to QS. Al-Baqarah (2): 180 â€Žas bayan takhsis, in the sense of a will as liability claims of â€ŽQS. Al-Baqarah (2): 180 is only allowed for people who do â€Žnot get the inheritance, so it is not as bayan al-naskh, because â€Žthe hadith can not disqualify verses of the Koran. Second, the â€Žlegal status of the â€œsanad hadithâ€ in the books of al-Shafi'iy is â€Žmunqatiâ€™, because Mujahid as the end of narrators was not a â€Žâ€Ž"sahabah". However, in the work of Abu Dawud, Ibn Majjah, â€Žal-Nasa'iy, and al-Tirmidhy, hadith such that boils down to â€Žtwo companions Abu â€˜Umamah and 'Amr ibn Kharijah so that â€Žits status as â€œhadith â€˜ahadâ€, and the status is â€œsahih li â€Žghayrihâ€, because of the support of various â€œmatn al-hadithâ€.â€Ž Abstrak: Artikel ini bermula dari, pertama, bagaimana â€Žpandangan Imam al-Shafiâ€˜i tentang kedudukan hadith â€œla â€Žwasiyya li warithâ€ terhadap QS. Al-Baqarah (2): 180, dan â€Žkedua, bagaimana status hukum sanad dan matan hadith â€Žtersebut. dengan pendekatan kualitatif dan anilisis verifikatif â€Žhirearkis, maka disimpulkan: pertama, pandangan Imam al-â€ŽShafiâ€˜i tentang kedudukan hadith â€œla wasiyya li warithâ€ â€Žterhadap QS. Al-Baqarah (2): 180 sebagai bayan takhsis, â€Ždalam arti wasiat sebagai tuntutan kewajiban QS. Al-Baqarah â€Žâ€Ž(2): 180 hanya dibolehkan untuk orang yang tidak â€Žmendapatkan bagian waris, sehingga bukan sebagai bayan al-â€Žnaskh karena hadith tidak bisa menasakh ayat al-Qurâ€™an. â€ŽKedua, status hukum sanad hadith tersebut dalam semua â€Žkitab karya al-Shafiâ€˜i adalah munqatiâ€˜, karena mujahid sebagai â€Žperawi puncak bukan sahabat. Namun, dalam karya Abu â€ŽDawud, Ibn Majah, al-Nasaâ€™i, dan al-Tirmidhi hadith tersebut â€Žbermuara pada dua sahabat Abu Umamah dan â€˜Amr bin â€ŽKharijah sehingga statusnya sebagai hadith ahad, dan â€Žberstatus sahih li ghayrih karena mendapatkan dukungan â€Žmatan-matan hadith yang berbeda.â€Ž